Galaxy formation in the Planck Millennium: the atomic hydrogen content of dark matter haloes. Issue 4 (18th December 2018) - Baugh, C M; Gonzalez-Perez, Violeta; Lagos, Claudia D P; Lacey, Cedric G; Helly, John C; Jenkins, Adrian; Frenk, Carlos S; Benson, Andrew J; Bower, Richard G; Cole, Shaun
ABSTRACT: We present recalibrations of thegalform semi-analytical model of galaxy formation in a new N -body simulation with the Planck cosmology. The Planck Millennium simulation uses more than 128 billion particles to resolve the matter distribution in a cube of 800 Mpc on a side, which contains more than 77 million dark matter haloes with mass greater than 2.12 × 10 9 h −1 M⊙ at this day. Only minor changes to a very small number of model parameters are required in the recalibration. We present predictions for the atomic hydrogen content (H i ) of dark matter haloes, which is a key input into the calculation of the H i intensity mapping signal expected from the large-scale structure of the Universe. We find that the H i mass–halo mass relation displays a clear break at the halo mass above which AGN heating suppresses gas cooling, ≈3 × 10 11 h −1 M⊙ . Below this halo mass, the H i content of haloes is dominated by the central galaxy; above this mass it is the combined H i content of satellites that prevails. We find that the H i mass–halo mass relation changes little with redshift up toz = 3. The bias of H i sources shows a scale dependence that gets more pronounced with increasing redshift.